Technology Entrepreneurship Project (ENT 600) : Under Armour / Muhammad Adam Ikhwan Azizan - Azizan, Muhammad Adam Ikhwan (2021)
This case study is to learn the creativity from myself. As a student, everyone is required to complete this case study. I’m interest about Under Armour company. In this case study, the first I search is the company background such as the founder, founded date and the place started. Next, this case study it contains specific of topic analysis which is covers the background, organization structure, mission, vision, and the products that been release from Under Armour company. Lastly, in this case study I identified the strength, weakness, opportunity and threat of the company and products. From the SWOT analysis I find the solution for the weakness. I got new knowledge about the material that suitable for the futsal shoes. From this analysis I got more experiences in searching problem and the solution for the company and products.